Step
*
1
1
1
of Lemma
howard-bar-rec-equal-spector
.....failed on: 16..... 
1. j : ℤ
2. 0 < j
3. ∀n:ℕ. ∀s,ind,base,mon,M:Base.
     (λhoward-bar-rec,n,s. case M n s
                           of inl(x) =>
                           let k,p = x 
                           in base n s (mon n k s p)
                           | inr(x) =>
                           ind n s (λt.(howard-bar-rec (n + 1) s.t@n))^j - 1 
      ⊥ 
      n 
      s ≤ fix((λspector-bar-rec,n,s. if if M n s then 0 else n + 1 fi  ≤z n
                                    then case M n s of inl(x) => let k,p = x in base n s (mon n k s p) | inr(x) => ⊥
                                    else ind n s (λt.(spector-bar-rec (n + 1) s.t@n))
                                    fi )) 
          n 
          s)
4. n : ℕ
5. s : Base
6. ind : Base
7. base : Base
8. mon : Base
9. M : Base
⊢ case M n s
   of inl(x) =>
   let k,p = x 
   in base n s (mon n k s p)
   | inr(x) =>
   ind n s 
   (λt.(λhoward-bar-rec,n,s. case M n s
                             of inl(x) =>
                             let k,p = x 
                             in base n s (mon n k s p)
                             | inr(x) =>
                             ind n s (λt.(howard-bar-rec (n + 1) s.t@n))^j - 1 
        ⊥ 
        (n + 1) 
        s.t@n)) ≤ if if M n s then 0 else n + 1 fi  ≤z n
  then case M n s of inl(x) => let k,p = x in base n s (mon n k s p) | inr(x) => ⊥
  else ind n s 
       (λt.(fix((λspector-bar-rec,n,s. if if M n s then 0 else n + 1 fi  ≤z n
                                      then case M n s of inl(x) => let k,p = x in base n s (mon n k s p) | inr(x) => ⊥
                                      else ind n s (λt.(spector-bar-rec (n + 1) s.t@n))
                                      fi )) 
            (n + 1) 
            s.t@n))
  fi 
BY
{ AssumeHasValue }
1
1. j : ℤ
2. 0 < j
3. ∀n:ℕ. ∀s,ind,base,mon,M:Base.
     (λhoward-bar-rec,n,s. case M n s
                           of inl(x) =>
                           let k,p = x 
                           in base n s (mon n k s p)
                           | inr(x) =>
                           ind n s (λt.(howard-bar-rec (n + 1) s.t@n))^j - 1 
      ⊥ 
      n 
      s ≤ fix((λspector-bar-rec,n,s. if if M n s then 0 else n + 1 fi  ≤z n
                                    then case M n s of inl(x) => let k,p = x in base n s (mon n k s p) | inr(x) => ⊥
                                    else ind n s (λt.(spector-bar-rec (n + 1) s.t@n))
                                    fi )) 
          n 
          s)
4. n : ℕ
5. s : Base
6. ind : Base
7. base : Base
8. mon : Base
9. M : Base
10. (case M n s
 of inl(x) =>
 let k,p = x 
 in base n s (mon n k s p)
 | inr(x) =>
 ind n s 
 (λt.(λhoward-bar-rec,n,s. case M n s
                           of inl(x) =>
                           let k,p = x 
                           in base n s (mon n k s p)
                           | inr(x) =>
                           ind n s (λt.(howard-bar-rec (n + 1) s.t@n))^j - 1 
      ⊥ 
      (n + 1) 
      s.t@n)))↓
⊢ case M n s
   of inl(x) =>
   let k,p = x 
   in base n s (mon n k s p)
   | inr(x) =>
   ind n s 
   (λt.(λhoward-bar-rec,n,s. case M n s
                             of inl(x) =>
                             let k,p = x 
                             in base n s (mon n k s p)
                             | inr(x) =>
                             ind n s (λt.(howard-bar-rec (n + 1) s.t@n))^j - 1 
        ⊥ 
        (n + 1) 
        s.t@n)) ≤ if if M n s then 0 else n + 1 fi  ≤z n
  then case M n s of inl(x) => let k,p = x in base n s (mon n k s p) | inr(x) => ⊥
  else ind n s 
       (λt.(fix((λspector-bar-rec,n,s. if if M n s then 0 else n + 1 fi  ≤z n
                                      then case M n s of inl(x) => let k,p = x in base n s (mon n k s p) | inr(x) => ⊥
                                      else ind n s (λt.(spector-bar-rec (n + 1) s.t@n))
                                      fi )) 
            (n + 1) 
            s.t@n))
  fi 
2
1. j : ℤ
2. 0 < j
3. ∀n:ℕ. ∀s,ind,base,mon,M:Base.
     (λhoward-bar-rec,n,s. case M n s
                           of inl(x) =>
                           let k,p = x 
                           in base n s (mon n k s p)
                           | inr(x) =>
                           ind n s (λt.(howard-bar-rec (n + 1) s.t@n))^j - 1 
      ⊥ 
      n 
      s ≤ fix((λspector-bar-rec,n,s. if if M n s then 0 else n + 1 fi  ≤z n
                                    then case M n s of inl(x) => let k,p = x in base n s (mon n k s p) | inr(x) => ⊥
                                    else ind n s (λt.(spector-bar-rec (n + 1) s.t@n))
                                    fi )) 
          n 
          s)
4. n : ℕ
5. s : Base
6. ind : Base
7. base : Base
8. mon : Base
9. M : Base
10. is-exception(case M n s
 of inl(x) =>
 let k,p = x 
 in base n s (mon n k s p)
 | inr(x) =>
 ind n s 
 (λt.(λhoward-bar-rec,n,s. case M n s
                           of inl(x) =>
                           let k,p = x 
                           in base n s (mon n k s p)
                           | inr(x) =>
                           ind n s (λt.(howard-bar-rec (n + 1) s.t@n))^j - 1 
      ⊥ 
      (n + 1) 
      s.t@n)))
⊢ case M n s
   of inl(x) =>
   let k,p = x 
   in base n s (mon n k s p)
   | inr(x) =>
   ind n s 
   (λt.(λhoward-bar-rec,n,s. case M n s
                             of inl(x) =>
                             let k,p = x 
                             in base n s (mon n k s p)
                             | inr(x) =>
                             ind n s (λt.(howard-bar-rec (n + 1) s.t@n))^j - 1 
        ⊥ 
        (n + 1) 
        s.t@n)) ≤ if if M n s then 0 else n + 1 fi  ≤z n
  then case M n s of inl(x) => let k,p = x in base n s (mon n k s p) | inr(x) => ⊥
  else ind n s 
       (λt.(fix((λspector-bar-rec,n,s. if if M n s then 0 else n + 1 fi  ≤z n
                                      then case M n s of inl(x) => let k,p = x in base n s (mon n k s p) | inr(x) => ⊥
                                      else ind n s (λt.(spector-bar-rec (n + 1) s.t@n))
                                      fi )) 
            (n + 1) 
            s.t@n))
  fi 
Latex:
Latex:
.....failed  on:  16..... 
1.  j  :  \mBbbZ{}
2.  0  <  j
3.  \mforall{}n:\mBbbN{}.  \mforall{}s,ind,base,mon,M:Base.
          (\mlambda{}howard-bar-rec,n,s.  case  M  n  s
                                                      of  inl(x)  =>
                                                      let  k,p  =  x 
                                                      in  base  n  s  (mon  n  k  s  p)
                                                      |  inr(x)  =>
                                                      ind  n  s  (\mlambda{}t.(howard-bar-rec  (n  +  1)  s.t@n))\^{}j  -  1 
            \mbot{} 
            n 
            s  \mleq{}  fix((\mlambda{}spector-bar-rec,n,s.  if  if  M  n  s  then  0  else  n  +  1  fi    \mleq{}z  n
                                                                        then  case  M  n  s
                                                                                    of  inl(x)  =>
                                                                                    let  k,p  =  x 
                                                                                    in  base  n  s  (mon  n  k  s  p)
                                                                                    |  inr(x)  =>
                                                                                    \mbot{}
                                                                        else  ind  n  s  (\mlambda{}t.(spector-bar-rec  (n  +  1)  s.t@n))
                                                                        fi  )) 
                    n 
                    s)
4.  n  :  \mBbbN{}
5.  s  :  Base
6.  ind  :  Base
7.  base  :  Base
8.  mon  :  Base
9.  M  :  Base
\mvdash{}  case  M  n  s
      of  inl(x)  =>
      let  k,p  =  x 
      in  base  n  s  (mon  n  k  s  p)
      |  inr(x)  =>
      ind  n  s 
      (\mlambda{}t.(\mlambda{}howard-bar-rec,n,s.  case  M  n  s
                                                          of  inl(x)  =>
                                                          let  k,p  =  x 
                                                          in  base  n  s  (mon  n  k  s  p)
                                                          |  inr(x)  =>
                                                          ind  n  s  (\mlambda{}t.(howard-bar-rec  (n  +  1)  s.t@n))\^{}j  -  1 
                \mbot{} 
                (n  +  1) 
                s.t@n))  \mleq{}  if  if  M  n  s  then  0  else  n  +  1  fi    \mleq{}z  n
    then  case  M  n  s  of  inl(x)  =>  let  k,p  =  x  in  base  n  s  (mon  n  k  s  p)  |  inr(x)  =>  \mbot{}
    else  ind  n  s 
              (\mlambda{}t.(fix((\mlambda{}spector-bar-rec,n,s.  if  if  M  n  s  then  0  else  n  +  1  fi    \mleq{}z  n
                                                                            then  case  M  n  s
                                                                                        of  inl(x)  =>
                                                                                        let  k,p  =  x 
                                                                                        in  base  n  s  (mon  n  k  s  p)
                                                                                        |  inr(x)  =>
                                                                                        \mbot{}
                                                                            else  ind  n  s  (\mlambda{}t.(spector-bar-rec  (n  +  1)  s.t@n))
                                                                            fi  )) 
                        (n  +  1) 
                        s.t@n))
    fi 
By
Latex:
AssumeHasValue
Home
Index